Menarche Anxiety Judging from the Role of Parents and Attitudes of Sunan Ampel Junior High School Students in Pagelaran - Fauzia, Parastika Anggun; Anggraeni, Suci; Korbaffo, Anita Restu (Master of Public Health Program Universitas STRADA Indonesia, 2021)
The high menarche anxiety that occurs in young women in term of parents role and teenagers attitude. Purpose to analyze the relationship between parents role and teenagers attitudes about menarche anxiety in Sunan Ampel junior high school. Methods: this study is a quantitative correlation with cross sectional analytic. the samples in this study were 29 female students in sunan ampel junior high school, the variable are parent role and teenagers attitude, and the dependent variable is menarche anxiety. Methods of data analysis using Chi-Square test. Results: most of parents roles about menarche were negative (58.6%), most of the teenagers attitudes about menarche were negative (62.1%), the majority of teenagers did not experience menarche anxiety (51.7%), there is a relationship between parents role with the menarche anxiety in Sunan Ampel Pagelaran junior high school (Asymp. Sig-tailed 0.004), There is a relationship between teenagers attitudes with menarche anxiety in Sunan Ampel junior high school (Asymp. Sig-tailed 0.011). Parent role and teenagers attitudes that tend to negative affect teenagers psychologically, causing anxiety due to unpreparedness and refusing menarche